M-N Homomorphism of an M-N Fuzzy Soft Subgroups and Its Level M-N Subgroups - Kaliraja, M.; Rumenaka, S. (Communications in Mathematics and Applications, 2022)
We examined the notion of M-N homomorphism of fuzzy soft subgroups in this study, then defined the M-N level subsets of a fuzzy soft subgroup and discussed some of its basic aspects.
Keywords: Fuzzy group; M-N fuzzy group; M-N fuzzy soft subgroups; M-N level subset; M-N homomorphism of fuzzy soft subgroups